Analisis Kesesuaian Layanan Kereta Api PSO (Public Service Obligation) Antarkota Terhadap Standar Pelayanan Minimum (Studi Kasus Periode Triwulan I dan Triwulan II Tahun 2023 di Pulau Jawa) (Politeknik Perkeretaapian Indonesia Madiun, 2023)
The train mode has advantages over other transportation modes, especially road-based modes. Railways need to be developed by the government to improve people’s welfare, one of which is by implementing Public Service Obligation (PSO) by compensate the fares difference on several train services. In its implementation, rolling stocks operator must meet the minimum service standard. Therefore, this research is conducted to analyze the suitability of the services compared to the minimum service standards in each quarter. The research methods used is a survey of the physical condition of the intercity PSO rollingstocks in Java Island compared to the minimum service standards in Ministry of Transportation Regulation No. PM 63 of 2019 which was carried out in Quarter I and Quarter II. Based on the results of the survey and identification, it was found that in general the intercity PSO train services in Java Island are in accordance with the minimum service standard, with a few findings about CCTV, fire extingusher, lighting, and toilet that have been fixed.